ChemInform Abstract: Regio‐ and Diastereoselective Synthesis of Highly Substituted, Oxygenated Piperidines from Tetrahydropyridines. Issue 46 (November 2015) - Chen, Shuming; Mercado, Brandon Q.; Bergman, Robert G.; Ellman, Jonathan A.
Abstract This preparation of piperidine derivatives relies on the epoxidation of tetrahydropyridines as the key reaction.